Human-macaque conflict between tourists and long- tailed macaques in Kanching Recreational Forest, Rawang, Selangor, Malaysia - A. Sadili, Diana Rose (2016)
Introduction: One of the most widespread primate groups in the world is the genus Macaca. The continuous overlap between macaques and humans has created complex conflicts which are brought by a variety of factors that may influence how macaques and humans interact. These include features of the location and history of interaction between people and macaques at a site. The interaction between humans and macaques may vary in response to the degree of overlap in physical space, macaque’s hunger, thirst and or changes in season. Macaques’ interaction with humans may also be more motivated based on prior experiences, surrounding, feeding, harassment and other forms of contact with humans. Objective: The objective of the study is to assess the existing human-macaque conflicts and to identify the common factors that influence the conflicts between humans and macaques at Kanching Recreational Forest. Methods: Tourists and long-tailed macaques’ behaviour and activities were observed from 0800 hours to 1830 hours from February 2015 to July 2015 using scan and ad libitum sampling. The researcher conducted preliminary non-formal observations on October 2014. Survey questionnaires were used to gather information related to tourists’ perceptions towards macaques; and target sampling was applied. Key informants were also interviewed (e.g. management staff) to fill the data gaps. Result: The results from the Spearman’s correlation analyses (p<0.05) revealed that the number of tourist was associated with the appearances of long-tailed macaques- as the number of tourists increased, the number of macaques’ appearances also increased. Although no incidence of biting was observed, there were 2,210 cases of snatching and 727 cases of aggression from the monkeys to the park tourists. Using two-sample Ztest, results also indicated that adult male macaques were the most aggressive group (z=0.077394, p<0.05). Provision of food was the main factor of conflicts.Conclusion: Human-macaque conflicts were associated with factors such as increase of tourists; and the construction work around the park. Results also show that tourists’ behaviour and activities towards macaques, and natural behaviour of macaques such as playfulness, aggression and attraction to food cause the conflicts. Furthermore, tourists’ lesser direct contact with macaques and non provision of food decrease humanmacaque interactions which will also more likely decrease the conflicts. Several suggestions for the management of macaques were made based on the results of this study. These suggestions include: information dissemination among tourists and park’s management on macaques’ behaviour and its potential risks to humans, enforcement of rules and regulations inside the park, control of food entry in the park and sterilization, capture or relocation of macaques.